Radio Frequency MRI coils - Truszkiewicz, Adrian; Aebisher, David; Bober, Zuzanna; Ożóg, Łukasz; Bartusik-Aebisher, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Magnetic Resonance Imaging (MRI) coils technology is a powerful improvement for clinical diagnostics. This includes opportunities for mathematical and physical research into coil design. Aim. Here we present the method applied to MRI coil array designs. Material and methods. Analysis of literature and self-research. Results. The coils that emit the radiofrequency pulses are designed similarly. As much as possible, they deliver the same strength of radiofrequency to all voxels within their imaging volume. Surface coils on the other hand are usually not embedded in cylindrical surfaces relatively close to the surface of the body. Conclusion. The presented here results relates to the art of magnetic resonance imaging (MRI) and RF coils design. It finds particular application of RF coils in conjunction with bore type MRI scanners.
Keywords: field strength 1.5 Tesla; magnetic resonance imaging; radio frequency coil